Panel regression analysis of the link between ESG indicators and financial performance in the energy and transportation Industry of ASEAN 5 countries: A sectoral perspective - Arellano, Rafael Antonio C. (Animo Repository, 2023)
This study focuses on how environmental, social, and governance (ESG) factors affect the financial success of the energy and transportation industries in the ASEAN-5 nations. The researchers want to know if businesses with higher ESG scores perform better financially than those with lower scores. The study's conclusions have implications for the energy and transportation industries in the ASEAN-5 nations, offering guidance on how to enhance their ESG practices to boost financial performance and draw in socially conscious investors. The study examined the relationship between ESG metrics and financial performance in the energy and transportation sectors of the ASEAN 5 nations using panel data analysis and a quadratic linear regression model. The study took into account different financial performance indicators and ESG measures while controlling for firm-specific traits over a 4-year period from 2019 to 2022. The statistical model of choice allowed for a more thorough comprehension of the nonlinear relationship between ESG ratings and company financial performance, offering insightful information for future forecasts and evaluations in the fields of business, finance, and economics.